2021
DOI: 10.1111/jac.12511
|View full text |Cite
|
Sign up to set email alerts
|

Low absorption of silicon via foliar in comparison to root application has an immediate antioxidant effect in mitigating water deficit damage in sugarcane

Abstract: High root absorption of silicon (Si) in sugarcane plants that accumulate the element attenuates water deficit-induced damage. However, there is a lack of research to identify whether the low relative absorption of Si via leaf spraying compared to root application has an immediate antioxidant effect on plants under water restriction. For How to cite this article: Teixeira GCM, de Mello Prado R, Rocha AMS. Low absorption of silicon via foliar in comparison to root application has an immediate antioxidant effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…There is little evidence of the beneficial effects of Si on plants grown without specific nutritional disorders. Nevertheless, some reports indicate the positive effects of Si on crops under biotic 12 or abiotic stresses 14 , 17 . In the present study, the beneficial effect of Si on dry matter production was evident even in plants grown without nutritional deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little evidence of the beneficial effects of Si on plants grown without specific nutritional disorders. Nevertheless, some reports indicate the positive effects of Si on crops under biotic 12 or abiotic stresses 14 , 17 . In the present study, the beneficial effect of Si on dry matter production was evident even in plants grown without nutritional deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these beneficial effects have been recorded in plants under biotic stress 12 . Studies addressing abiotic stresses refer to damage by salinity 13 and water conditions 11 , 14 , 15 . Regarding nutritional disorders, studies have focused on the benefit of Si in relieving nitrogen (N) deficiency in rice 16 , potassium (K) deficiency in sorghum 17 and maize 18 , magnesium (Mg) deficiency in maize 19 , calcium (Ca) deficiency in cabbage 20 and rocket 21 , phosphorus (P) deficiency in sorghum 22 , wheat 23 , and cucumber 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…This nding has important practical implications as it should expand the use of Si in irrigated sugarcane crops, given the low amount of Si used, close to 20 kg ha −1 , in relation to other sources of lower solubility such as calcium silicate, which requires doses above 1000 kg ha −1 20 . Previous reports have already shown the e ciency of Si fertigation in optimizing the uptake of this element in forage plants 22 and pre-sprouted sugarcane seedlings 17 .…”
Section: Discussionmentioning
confidence: 97%
“…This is because fertigation allows the use of a solution with concentrations below 3 mmol L −1 Si, avoiding the occurrence of polymerization 21 . Previous studies have shown the e ciency of Si fertigation in optimizing the absorption of this element in forage plants 22 and in pre-sprouted sugarcane seedlings 17 . However, there is a lack of studies in plant cane, especially in phases with high relative growth rates, which can occur between 84 and 135 days after transplanting 7 depending on genotype and growing conditions 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation